Effect of Chiranjeevi Yojana on institutional deliveries and neonatal and maternal outcomes in Gujarat, India: a difference-in-differences analysis - Manoj Mohanan; Sebastian Bauhoff; Gerard La Forgia; Kimberly Singer Babiarz; Kultar Singh; Grant Miller (The World Health Organization, 2014)
Objective To evaluate the effect of the Chiranjeevi Yojana programme, a public-private partnership to improve maternal and neonatal health in Gujarat, India. Methods A household survey (n = 5597 households) was conducted in Gujarat to collect retrospective data on births within the preceding 5 years. In an observational study using a difference-in-differences design, the relationship between the Chiranjeevi Yojana programme and the probability of delivery in health-care institutions, the probability of obstetric complications and mean household expenditure for deliveries was subsequently examined. In multivariate regressions, individual and household characteristics as well as district and year fixed effects were controlled for. Data from the most recent District Level Household and Facility Survey (DLHS-3) wave conducted in Gujarat (n = 6484 households) were used in parallel analyses. Findings Between 2005 and 2010, the Chiranjeevi Yojana programme was not associated with a statistically significant change in the probability of institutional delivery (2.42 percentage points; 95% confidence interval, CI: −5.90 to 10.74) or of birth-related complications (6.16 percentage points; 95% CI: −2.63 to 14.95). Estimates using DLHS-3 data were similar. Analyses of household expenditures indicated that mean household expenditure for private-sector deliveries had either not fallen or had fallen very little under the Chiranjeevi Yojana programme. Conclusion The Chiranjeevi Yojana programme appears to have had no significant impact on institutional delivery rates or maternal health outcomes. The absence of estimated reductions in household spending for private-sector deliveries deserves further study.